Reproductive Tract Score: A Tool for Evaluating Beef Heifer Reproductive Potential - Mario Binelli; Thiago Martins; Cecilia Constantino Rocha; Felipe A. C. C. Silva; João Bittar; Philipe Moriel; Angela Gonella-Diaza; Lauren Butler; Cindy Sanders (EDIS)
This publication explains the RTS methodology and suggests how it can be implemented in a cow-calf operation. Written by Mario Binelli, Thiago Martins, Cecilia C. Rocha, Felipe A. C. C. Silva, João Bittar, Philipe Moriel, Angela M. Gonella-Diaza, Lauren Butler, and Cindy Sanders, and published by the UF/IFAS Department of Animal Sciences, October 2021.